Clustering and routing model for transport logistics using software agents. Issue 2 (1st January 2011) - Singh, Gulshanara; Görg, Carmelita; Timm-Giel, Andreas
Autonomous cooperation is an evolving trend in transport domain of logistics network. Integration of technologies like multi-agent systems and communication network strategies aids in bringing about autonomy and increased flexibility to handle complexity and dynamics in the network. A cluster-based Distributed Logistics Routing Protocol (DLRP) (Reketsbrink et al., 2008) approach is presented using the software-agent-based simulation framework. DLRP involves the route discovery process both by the packages as well as the vehicles simultaneously. The route discovery process by the vehicle and packages can result in enormous communication. A performance evaluation of this approach was presented in Singh et al. (2008a). However, this paper presents an enhancement of the analytical formulation and the analytical results are then compared with the simulation results.